Cervical intraepithelial neoplasia - Aidé, Susana; Almeida, Gutemberg; Vai, Isabel do; Vespa Junior, Nelson; Campaner, Adriana B. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Cervical intraepithelial neoplasia (CIN) represent one of subclinical manifestations by Human Papillomavirus (HPV) infection. Diagnostic and treatment of CIN are extremely important because they are related with the carcinogenesis of cervical cancer. This article attempts to carry out a review on the main epidemiological data, natural history, diagnostic and treatment of CIN.